Psychotherapy focusing on dialogical and narrative perspectives: a systematic review from qualitative and mixed-methods studies - Mellado, Augusto; del Río, María Teresa; Andreucci-Annunziata, Paola; Molina, María Elisa (Frontiers in Psychology, 2024)
Introduction This systematic review identified qualitative and mixed-methods empirical studies on psychotherapy from dialogical and narrative approaches, aiming to address the following questions: (1) How are subjectivity and intersubjectivity qualitatively understood in dialogical and/or narrative psychotherapies studied using dialogical and narrative approaches? (2) How do therapeutic changes occur, including their facilitators and barriers? (3) What psychotherapeutic resources are available for psychotherapists in these types of studies? Method The articles were selected according to the Systematic Reviews and Meta-Analyses (PRISMA) guidelines and the eligibility criteria proposed by the PICOS strategy (participants, interventions, comparators, outcomes, and study design) from 163 records identified in the Web of Science Core Collection databases. Results The systematic review process allowed the selection of 16 articles. The results provided insights into the understanding of subjectivity, intersubjectivity, change in psychotherapy, its facilitators, and barriers from these perspectives. It also offered some therapeutic interventions that can be implemented in psychotherapies, integrating dialogical and/or narrative aspects. Discussion The centrality of dialogical exploration of patient/client resources, therapists as interlocutors fostering client agency, polyphony serving as scaffolding for change, and interconnection with the sociocultural environment are discussed. The integration of this latter topic has been a challenge for these types of studies, considering the active construction of shared meanings. The dialogical and narrative approaches focus psychotherapy on transforming meanings through dialogue and re-authoring stories, evolving within cultural and historical contexts. Thus, this study highlights the relevance of these perspectives in contemporary psychotherapy, emphasizing dialogue in co-creation within an intersubjective framework.